Response of a land-terminating sector of the western Greenland Ice Sheet to early Holocene climate change: Evidence from 10Be dating in the Søndre Isortoq region. (15th January 2018) - Lesnek, Alia J.; Briner, Jason P.
Abstract: The prevalence of land-terminating Greenland Ice Sheet margins is expected to increase as tidewater glaciers retreat onto land, yet few studies have characterized the sensitivity of these slow-moving margins to climatic variability. The response of land-terminating ice sheet sectors to climate forcing can be assessed by examining records of paleo-ice margin positions preserved in ice sheet moraine systems. In western Greenland, the extensive Fjord Stade moraine system was deposited by minor readvances or stillstands of the Greenland Ice Sheet margin during early Holocene net recession. Here, we combine new moraine mapping and cosmogenic 10 Be exposure dating to constrain the timing of Fjord Stade moraine deposition in the Søndre Isortoq region. We find that the Fjord Stade moraines are composed of a western stage and an eastern stage, which we constrain to 9.7 ± 0.7 ka ( n = 7; 1 SD) and 9.0 ± 0.3 ka ( n = 7; 1 SD), respectively. Synchronous deposition of the Fjord Stade moraine complex across at least 350 km of western Greenland implies a widespread response of the western Greenland Ice Sheet to the 9.3 ka event. Furthermore, these new moraine ages may correlate with Laurentide Ice Sheet-sourced freshwater pulses into the North Atlantic Ocean. We also show that the response of the western Greenland Ice Sheet to early Holocene freshwater forcing was not restricted to fast-flowing, marine-terminating outlet glaciers; the land-terminating margin in the Søndre Isortoq region halted or reversed its pattern of retreat in response to climatic change. Highlights: We present a new 10 Be chronology of western Greenland's Fjord Stade moraines. Two moraine stages date to 9.8 ± 0.7 ka ( n = 7) and 9.0 ± 0.3 ka ( n = 7). A land-terminating region of the Greenland Ice Sheet responded to the 9.3 ka event. Moraine ages are coeval with episodes of freshwater input to North Atlantic Ocean.